Implications of corporate governance on financial performance: an analytical review of governance and social reporting reforms in India - Puneeta Goel (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2018)
Currently the corporate governance reforms in India are at cross roads where though the intention behind the reforms is good yet there is a need to look for a complete solution addressing country specific challenges in Indian context. Keeping pace with developments at international level, India also introduced reforms for improving corporate, social and environment disclosures. This paper explores the effectiveness of these corporate governance reforms by analyzing the corporate governance practices followed by Indian companies in two reform periods (FY 2012-13 as Period 1) and (FY 2015-16 as Period 2). Considering mandatory regulations as per clause 49 of Listing agreement with Securities exchange board of India and the governance norms in the new Company Act, 2013, a corporate governance performance (CGP) index is developed to measure corporate governance score of Indian companies. Though there is a significant improvement in corporate governance structures implied by Indian companies but the number of independent directors inducted in the board decreases after the reforms in period 2. All the sectors under study show a significant improvement in following corporate governance practices after the reforms. The study reported a significant relationship between integrated framework of total corporate social performance and financial performance only in period 1. Corporate governance reforms do not impact financial linkages in Indian market in period 2.
Keywords: 650; Corporate governance; Corporate governance and social responsibility reforms; Financial performance